VOICES FROM THE NINETEENTH-CENTURY: WOMEN TRAVELERS AND POLITICAL ACTIVISM - Leão, Juraci Andrade de Oliveira (Em Tese, 2003)
This study aims at analyzing some aspects in the diaries: Journal of a Voyage to Brazil, by the British Maria Graham, and Peregrinations of a Pariah, by the French-Peruvian Flora Tristan. This essay discusses how these women travelers transgressed the role ascribed to them in society through their intervention in the political sphereand how such aspects contribute to the construction of anew female identity.